THE IMPACT OF CULTURAL MENTALITY AND STATUTORY CENSORSHIP ON SLANG NEUTRALIZATION IN AUDIOVISUAL TRANSLATION - Qayimova Mohinur (International Journal of Literature and Language Studies, 2026)
Abstract. The rapid expansion of global video-on-demand (VOD) ecosystems has altered the paradigm of cross-cultural media consumption, presenting unique challenges for Audiovisual Translation (AVT). Slang, serving as a highly volatile, culture-specific carrier of subcultural identity and emotional intensity, sits at the center of this transformation. This paper investigates the dual-layered filtering process—comprising the mentality filter, which involves socio-cognitive and cultural frameworks, and the censorship filter, which encompasses legal, institutional, and self-imposed regulatory mechanisms. Together, these filters shape the translation of contemporary English audiovisual slang into structurally and culturally distinct target contexts. Utilizing comparative, descriptive, and content-analysis methodologies grounded in translation studies, this study evaluates the systematic shifts from original non-standard dialogue to translated subtitles and dubbing scripts. The findings indicate a pronounced systemic preference for domestication and euphemization, leading to a structural neutralization of slang expressions. This article serves as an academic guide for students and researchers analyzing the balance between source-text fidelity and target-market acceptability.